Pengaruh Pemberian Vitamin C dalam Pengobatan Covid-19 - Inas Dzakirah (Jurnal Medika Hutama, 2021)
Coronavirus Disease 2019 (Covid-19) is a new type of disease that was first reported in Wuhan City, this disease is transmitted by animals that cause disturbances in the human respiratory tract. Covid-19 patients are only treated symptomatically, including vitamin C. The purpose of this study was to determine the effect of giving vitamin C in the treatment of Covid-19. The method used in conducting this research is using qualitative methods in the form of literature studies from various national and international journals. The results in this study were that there was an effect of giving vitamin C in the Covid-19 treatment because there were 50 cases that patients who consumed vitamin C recovered faster than patients who did not consume vitamin C.